Cerebral cysticercosis in Campina Grande, Paraíba - northern Brazil: computerized tomography diagnosis importance Cisticercose cerebral em Campina Grande, Paraíba - Nordeste do Brasil: importância diagnóstica da tomografia computadorizada - Thiago D. Gonçalves-Coêlho; Matheus Diniz G. Coelho (Arquivos de Neuro-Psiquiatria)
Neurocysticercosis is the infection of the central nervous system by the larval form of Taenia solium , the Cysticercus cellulosae. We studied 4011 computerized tomographies performed in TomoHPI Radioimaging Service, Hospital Pedro I, Campina Grande PB, Northern Brazil, since its installation on August 1993 to July 1995. 41 patients were diagnosed as having Cysticercus cerebral infestation, corresponding to an incidence of 1.02%. No cases were related in Campina Grande PB during 1991 according to hospitalizations under prospective payment rates. After this radioimaging service installation, we observed 1.86 cases per month. We conclude that Campina Grande has to be included as an endemic area of neurocysticercosis, needing health service measures to cease the cycle Taenia-Cysticercus, the only way to get rid of such a serious problem. Neurocisticercose é a infecção do sistema nervoso central pela larva da Taenia solium, o Cysticercus cellulosae. Estudamos 4011 tomografias computadorizadas feitas no Serviço de Radioimagem do Hospital Pedro I, Campina Grande PB, desde sua instalação em setembro de 1993 a junho de 1995. 41 pacientes foram diagnosticados como apresentando infestação cerebral por Cysticercus, correspondendo a 1,02 % . Nenhum caso de neurocisticercose foi diagnosticado em Campina Grande no ano de 1991, ao se analisar as causas das internações na Rede Hospitalar de Campina Grande conveniada ao SUS durante tal ano. Após a instalação deste serviço de radioimagem, observamos, em média, 1,86 casos por mês. Concluímos ser Campina Grande área endêmica para neurocisticercose, necessitando de medidas de saúde pública no intuito de cessar o ciclo Taenia-Cysticercus, a única maneira de erradicar tal afecção.